SELECTION INDICES FOR GENETIC IMPROVEMENT OF HOLSTEIN FRIESIAN X GIR HALFBREDS - D. R. BIRARI, R. S. DENGRE D. K. DEOKAR (Indian Journal of Animal Production and Management, 2017)
The data pertaining to Holstein Friesian x Gir halfbreds were collected on firstlactation traits and classified according to generation, period of birth/calving, season ofbirth/calving and peak milk yield and analyzed by least squares method. Corrected datawere used for estimation of genetic and phenotypic correlation and heritability. Theeconomic weights of different traits were calculated. The relative economic value of different traits was obtained by considering the economic weight of FLMY as standardunit. The aggregate genetic economic gain (“H) and relative efficiency of the index wascomputed. Selection indices (21) were constructed by using different traits in differentcombinations. Index with four trait combination I5 [(-1.504)(AFC) + (0.337)(FLMY) + (-6.840) (FLL) + (2.412) (FCI)] and index with three trait combination I2 [(-1.305) (AFC) +(1.854) (FDP) + (-0.055) (FLMY)] were found to be the most useful indices. Using I5index the response in each trait per generation was expected to be decrease in age atfirst calving (228.80 days), increase in first lactation milk yield (521.04 kg), decrease infirst lactation length (50.31 days) and decrease in first calving interval (42.50 days).While using I2 index response in each trait per generation was expected to be 188.54days in age at first calving (AFC), 10.22 days in first dry period (FDP) and 73.39 kg infirst lactation milk yield (FLMY). Therefore, form these results it may be inferred that outof 21 selection indices constructed for HF x Gir halfbreds, index I5 from four traitscombination and I2 from three traits combination were found to be relatively efficientindices and rated as the most useful indices for their high reliability and expectedgenetic gain.Key word: Selection indices, genetic improvement and genetic gain.